When Journalism and Automation Intersect: Assessing the Influence of the Technological Field on Contemporary Newsrooms. (26th November 2019) - Wu, Shangyuan; Tandoc, Edson C.; Salmon, Charles T.
ABSTRACT: In this era of "big data", where information circulates in unprecedented amounts, this paper examines the use of automation in newsrooms to manage the data deluge—not from the perspective of newsworkers, but from the technologists driving these digital innovations instead. These technologists, in their work with journalists, have to learn about journalistic rules while carrying with them technology's own internal logic. Using field theory and in-depth interviews with leading technological firms in data science and management, this study maps out the principles and practices of the technological field and the pressures and powers it exerts on the journalistic field today. Study findings reveal the extent to which technological firms are able to impose their own logics on the journalistic field and become a potentially transformative force, challenging traditional conceptions of what journalism is.